Solutions exist for constraints to household production and retention of animal food products - Brown, D.L. (2003)
This article reviews constraints to household level animal source food production in developing countries and suggests solutions to some of these constraints. These constraints include land, labor, money, feed quality, water, disease, animal genetics, roles for animals beyond food production, grazing techniques and an understanding of the entire agricultural system at the household level. Better understanding of farming systems and the elements that comprise it which affect animal food production permits wise management of nutrient flows and enhanced sustainability